Understanding colour image: colour constancy - Liu, Bo-zhi (2018)
Human visual system has a mechanism which ensures that the perceived colour of an object remains almost constant under varying illumination conditions, and this mechanism is called colour constancy. Electronic imaging systems such as digital cameras do not naturally have this ability. The color appearance of images of an object under different lighting conditions changes with the colour of the light sources and this can cause problems in many computer vision applications such as object recognition. To deal with this problem, many algorithms have been developed to estimate the input image’s illuminant, and then recover the intrinsic colour of the scene correctly. In this thesis, we focus on this topic, try to produce new colour constancy algorithms in both images and videos, to improve the performance of the state of the art.